Newton's darkness two dramatic views - Djerassi, Carl 1923-2015 (Imperial College Press, 2003)
"What purpose is served by showing that England's greatest natural philosopher is flawed ... like other mortals?" asks one of the characters in Newton's Darkness. "We need unsullied heroes!" But what if the hero is sullied? At stake is an issue that is as germane today as it was 300 years ago: a scientist's ethics must not be divorced from scientific accomplishments. There is probably no other scientist of whom so many biographies and other historical analyses have been published than Isaac Newton - all of them in the standard format of documentary prose because of their didactic purpose to transmit historical information. Newton's Darkness, however, illuminates the darker aspects of Newton's persona through two historically grounded plays dealing with two of the bitterest struggles in the history of science. The name of Isaac Newton appears in virtually every survey of the public's choice for the most important persons of the second millennium.